Perancangan Basis Data Penjualan dengan Metode Database Lifecycle Pada Toko Lancar Elektrik - Yusuf Bahtiar; Dene Herwanto (Universitas Indraprasta PGRI Jakarta, 2022)
In this digitalization era, technology is growing rapidly over time. Technological advances have an impact on increasing effectiveness and efficiency in carrying out every job. Toko Lancar Elektrik as one of the stores on Jl. Kertabumi No.8 Karawang Kulon, offers or sells various electrical goods whose number of items increases annually. The problem that exists in Toko Lancar Elektrik is that the collection of the data of item sales and of the stock of goods is still conducted manually using notebooks. The purpose of this study is to use of database technology in selling goods so that the data can be stored quickly and easily and errors in data collection can be minimized. The results of the database design using the DBLC (DataBase Life Cycle) method with research aspects covering Database planning, System definition, Requirements collection and analysis, Database design, to implementation. The database design can have 4 types of entities, namely conceptual, logical, and physical in the form of information on goods, suppliers, orders, and sales. With this database design, it is expected that the goods recording can be more structured and easily to do.